'Zoella hasn't really written a book, she's written a cheque': Mainstream media representations of YouTube celebrities. (February 2020) - Deller, Ruth A; Murphy, Kathryn
In this article, we present a thematic analysis of broadcast and print media representations of YouTube celebrity. Youth-oriented media have capitalised on the phenomenon, placing vloggers alongside actors and pop stars. However, in much adult-oriented mainstream media, YouTubers are presented as fraudulent, inauthentic, opportunist and talentless, making money from doing nothing. Key themes recur in coverage, including YouTubers' presumed lack of talent and expertise, the alleged dangers they present and the argument that they are not 'really famous'. YouTubers' claims to fame are thus simultaneously legitimised by giving them coverage and delegitimised within said coverage, echoing media treatment of other 'amateur' celebrities such as reality stars and citizen journalists. We argue that the response to YouTubers in more traditional media outlets demonstrates recognition of their visibility and appeal to a younger audience, while also signifying apprehension towards a phenomenon that potentially threatens both the existence of traditional media forms, and the influence of traditional media professionals.